Comparison between two improvement methods to develop multipie insect resistance in common bean (Phaseolus vulgarís L.). - BUENO, JUAN MIGUEL; CARDONA, CÉSAR; QUINTERO, CONSTANZA MARÍA (Revista Colombiana de Entomología, 1999)
In order to incorporate multiple resistance to three major insect pests of common bean, the leafhopper, Einpoasa kraemeri Ross Moore (Homoptera: Cicadellidae ), the Mexican bean weevil. Zahrotes sublasciatu., (Boheman) (Coleoptera: Bruchidae) amid the bean pod weevil. Apion godmani (Wagner) (Coleoptera: Curculionidae), two improved methods were compared: Gamete Selections (G.S.) in early generations and selection of advanced lines. developed by Recombinant Inbred Unes (R.I.L.)method. In the G.S. method, the initial selection for resistance to Z. stilvascianis was done by means of detection in F, of the presence of porcelain. conditioning factor of resistance to this insect. Progenies positive for Marcelin were further submitted to various evaluations in the field for resistance to E. kroemeri in Colombia and (o A. godimani in Mexico. Of the 216 progenies selected for the presence of arcelin. 17 F_hiles were founri to combine resistance to the three insects. The R.I.L. did not have an early evaluation and were suhmitted to the attack of the three insects in F7. Laboratory tests with Z. sublusciants and field trials with E. kroeme ri and A. goclmani allowed to identify 23 F.lines. which combined the three resistances. Ir was concluded that the R.I.L. method allows the incorporation of multiple insect resistance with considerable savings in resources and time.